A huge verrucous carcinoma of the lower lip reconstructed by double Abbe flap: A case report and literature review - Chai, Ke; Liu, Jinbing; Xiao, Rong; Zhang, Guiying; Zhan, Yi (Frontiers in Oncology, 2023)
Lip verrucous carcinoma is a rare low-grade neoplasm, with an unsightly appearance and locally aggressive nature. Treatment of verrucous carcinoma is as yet challenging, no well-defined guidelines for effective and safe management of this disease are available. A case of a patient with a huge verrucous carcinoma of the lower lip successfully treated by surgical excision and double Abbe flap reconstruction technique is presented, and striking features of lip locations of this tumor as well as their management are discussed.